Jaguars of the dawn: spirit mediumship in the Brazilian Vale do Amanhecer - Pierini, Emily (Berghahn, 2020)
"The Brazilian Spiritualist Christian Order Vale do Amanhecer (Valley of the Dawn) is the place where the worlds of the living and the spirits merge and the boundaries between lives are regularly crossed. Drawing upon over a decade of extensive fieldwork in temples in Brazil and Europe, the author explores how mediums understand their experiences and how they learn to establish relationships with their spirit guides. She sheds light on the ways in which mediumistic development in the Vale do Amanhecer is used for therapeutic purposes and informs notions of body and self, of illness and wellbeing"--